Some Developments in the Prosecution of International Crimes Committedin Palestine: Any Real News? (Polish Yearbook of International Law, 2016)
This article examines the recent developments in the prosecution of international crimes committed in the Palestinian Territory, focusing mainly on the role of the International Criminal Court. The author analyses the Palestinian accession to the Rome Statute and the declarations issued pursuant to Art. 12(3) in order to verify whether it is possible to bring justice to Palestine through the prosecution of atrocities committed by both parties. The article pays great attention to the most recent events, such as the Prosecutor’s report on the Mavi Marmara incident and the subsequent decision of the Pre-Trial Chamber. Issues related to the Palestinian statehood are taken in account in relation to the interplay between international criminal justice and the Israeli-Palestinian conflict.